Analysis of Mobilization Factors, Personal Hygienic, Nutritional Status in Washing Perenium Healing in Women in Lamongan Health and Health Center - Siti Solikha; Siti Farida; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Perenium rupture is a tear that occurs in the perenium region during labor. Factors that influence the healing of perineal wounds include maternal nutritional needs that are sufficiently seen from the Body Mass Index (BMI), personal hygiene, mothers mobilizing. This study aims to determine the factors that influence the healing of perenium wounds in postpartum mothers at Turi Health Center and Lamongan Health Center in 2018. The research design used is quantitative research using a